Maslahah dan Efektifitas Pada Zakat Online Melalui Aplikasi Kitabisa: Sebuah Analisis Hukum - Okto Viandra Arnes (LPPM UIN Saizu Purwokerto, 2022)
Zakat is a property owned by Muslims who when they have reached their lineage, they must be issued zakat and given to mustahik in accordance with the command of Allah SWT. Zakat has been commanded by Allah SWT the Qur’an and Hadith. Seeing today’s developments, Zakat payments do not have to come directly to the zakat agency, but can be done online our through social media. The prsence of online institutions for Zakat management will make it easier for people to pay zakat. One of the most popular applications for zakat management is the Kitabisa application. The Kitabisa application was present in 2013 with the aim of collecting zakat from the community to be distributed to those who are entitled to receive it. In 2019 our applications can improve its managethment and distribution to the public. This study uses a normative juridical method with a descriptive analysis approach. The data colection technique of this research is library research. This study aims to analyze the benefits and effectiveness of online zakat through the Kitabisa application. The result of this study is that zakat online Kitabisa application is very useful and effective to do. Because someone who pays zakat does not have to come to the zakat amil body directly. Keywords: Online Zakat, Maslahah, Kitabisa, Legal Islamic Analysis.